(3OYGA TQjas
(3ChdgG (B:s
(3Gddge Efi CSFdc HYRI EYJRGR YRJc HWhd Mhd TOjO bhJc s
(3BNQgG (B:s
(3Gddge ELYdfG ai gPg GdSGYI jG bjhe HQMeJc GSJZjK aCZKfi hfLfi ef GdfGQ jG cQje hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydi MahX (B_ (3HZOGO (B(198) s
Keywords: (3GdeLGejYs